2017
DOI: 10.1007/s10803-017-3421-9
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Controlled Trial of the ACCESS Program: A Group Intervention to Improve Social, Adaptive Functioning, Stress Coping, and Self-Determination Outcomes in Young Adults with Autism Spectrum Disorder

Abstract: The purpose of this pilot randomized controlled trial was to investigate the acceptability and efficacy of the Acquiring Career, Coping, Executive control, Social Skills (ACCESS) Program, a group intervention tailored for young adults with autism spectrum disorder (ASD) to enhance critical skills and beliefs that promote adult functioning, including social and adaptive skills, self-determination skills, and coping self-efficacy. Forty-four adults with ASD (ages 18-38; 13 females) and their caregivers were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 94 publications
1
71
0
7
Order By: Relevance
“…Kenworthy et al's (2014) Unstuck and On Target program targets autistic EF difficulties through a cognitive behavioral program that teaches autistic school-age children self-regulatory EF scripts (e.g., Bstuck on a detail^, Bbig picture^, Bflexible thinking^) and how to deploy these scripts across different contexts in order to guide flexible, goal-directed behavior. A randomized controlled trial that tested the effectiveness of this program against a social skills intervention demonstrated that, while 7-to 11-year-old autistic children in both interventions improved, especially with regard to social skills, there were greater gains for those children who received the Unstuck and On Target program, including better EF skills (problem-solving, flexibility, and planning), as well as improved classroom behavior (following rules, making transitions and being flexible) (see also Oswald et al 2018, for a program in adults that includes executive function as a key focus). While Kenworthy et al's results are extremely encouraging, the findings from the current study suggest that we need to extend EF interventions into the preschool perioda time when the pre-frontal cortex shows a boost in development (Diamond 2013) and may have the greatest chance of influencing a range of important, concurrent skills, including school readiness (Blair and Razza 2007;Pellicano et al 2017), play (Faja et al 2016) and theory of mind (Hughes 1998;Pellicano 2010), as well as later behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Kenworthy et al's (2014) Unstuck and On Target program targets autistic EF difficulties through a cognitive behavioral program that teaches autistic school-age children self-regulatory EF scripts (e.g., Bstuck on a detail^, Bbig picture^, Bflexible thinking^) and how to deploy these scripts across different contexts in order to guide flexible, goal-directed behavior. A randomized controlled trial that tested the effectiveness of this program against a social skills intervention demonstrated that, while 7-to 11-year-old autistic children in both interventions improved, especially with regard to social skills, there were greater gains for those children who received the Unstuck and On Target program, including better EF skills (problem-solving, flexibility, and planning), as well as improved classroom behavior (following rules, making transitions and being flexible) (see also Oswald et al 2018, for a program in adults that includes executive function as a key focus). While Kenworthy et al's results are extremely encouraging, the findings from the current study suggest that we need to extend EF interventions into the preschool perioda time when the pre-frontal cortex shows a boost in development (Diamond 2013) and may have the greatest chance of influencing a range of important, concurrent skills, including school readiness (Blair and Razza 2007;Pellicano et al 2017), play (Faja et al 2016) and theory of mind (Hughes 1998;Pellicano 2010), as well as later behavior.…”
Section: Discussionmentioning
confidence: 99%
“…SST addresses social processes holistically, integrating didactic lessons, peer modeling, and behavioral rehearsal. Findings regarding the efficacy of SST to address anxiety and depression are mixed; several reviews of SST highlight unsuccessful attempts to address anxiety [80] and depression [81] as secondary treatment targets. In contrast, researchers examining the impact of a theatre-based SST intervention reported a concurrent decrease in anxiety in individuals with ASD [82] and group-based SST contributed to reduced depression linked to increased social contact [43].…”
Section: Identifying and Engaging Common Factorsmentioning
confidence: 99%
“…Preliminary support is also appearing for some programmes tailored specifically for the early years of adulthood. A novel skills training programme addressing challenges faced by young adults with ASD has shown preliminary positive effects [40], as has a group-delivered transition service for adults with ASD [41]. Similarly, a programme teaching parents to advocate for adult disability services seems to have the potential to empower parents [42].…”
Section: Introductionmentioning
confidence: 99%